Case study on the hybrid business model: KT's OTS - Minzheong Song (International Telecommunications Society (ITS), 2011)
This paper aims to analyze hybrid consumer behavior and develop a hybrid business model, which serves as a guideline to better understanding hybrid consumer behavior and their needs. The case is the telecommunication operator's new hybrid set-top-box business model which combines IPTV with DTH satellite reception and business. This paper shows KT's OTS (Olleh TV Skylife) which has a successful market performance so far with the hybrid Set Top Box (STB). Before this regional study, it shows the current status of Korean pay TV market in overview. After this, it analyzes the service offerings of cable TV, satellite TV and IPTV. Then, it shows that the mixed service portfolio of satellite TV and IPTV is the perfect service combination to beat the cable TV in terms of hybrid consumer needs. This paper also verifies that this hybrid business model generates good market performance and operating synergy with KT's other legacy business. In conclusion, this paper expects KT's vision about the future growth potential of OTS in home shopping, advertising sales based on the total subscriber base, and also KT's plan to make TV much smarter with innovative open business models such as TV application store of parent KT.
Keywords: 330; Hybrid business model; IPTV; Satellite TV